Effect of apigenin isolated from Aster yomena against Candida albicans: apigenin-triggered apoptotic pathway regulated by mitochondrial calcium signaling. (1st March 2019) - Lee, Wonjong; Woo, Eun-Rhan; Lee, Dong Gun
Abstract: Ethnopharmacological relevance: Aster yomena, a perennial herb that grows mainly in South Korea, has been employed in the traditional temple food for antibiotic efficacy. Recently, it was reported that apigenin isolated from A. yomena has a physical antifungal mechanism targeting membrane against Candida albicans . Aim of the study: Our study aimed to investigate the biochemical responses underlying the antifungal activity of apigenin isolated from A. yomena due to lack studies reporting the investigation of intracellular responses of apigenin in C. albicans . Materials and methods: Apigenin was isolated from the aerial parts of A. yomena . To evaluate apigenin-induced inhibitory effects and membrane damages, the measurement of the cell viability assay and the flux of cytosolic components were performed with at various concentrations. Intracellular external potassium and calcium levels were assayed by an ion-selective electrode meter, Fura2-AM and Rhod2-AM, respectively. Mitochondrial dysfunctions were analyzed by using JC-1, Mitotracker Green FM, and MitoSOX Red dye. H2 DCFDA, glutathione, and MDA assay were used to detect oxidative damage. Also, flow cytometry was carried out to detect apoptotic hallmarks using Annexin V-PI, TUNEL, and FITC-VAD-FMK staining. Tetraethylammoniumchloride (TEA), Ruthenium red (RR), and N -acetylcysteine (NAC) were used as a potassium channel blocker, mitochondrial calcium uptake inhibitor, and reactive oxygen species (ROS) scavenger, respectively. Results: We confirmed that there was no decrease of cell survival percentages in crude extracts of A. yomena treatment, however, only isolated apigenin has the antifungal effect in C. albicans . Apigenin triggered a dose-dependent mitochondrial calcium uptake followed by mitochondrial dysfunction, loss of the membrane potential and an increase in the mitochondrial mass and ROS. Apigenin also induced intracellular redox imbalance as indicated by the ROS accumulation, glutathione oxidation, and lipid peroxidation. Interestingly, NAC failed the restore the mitochondrial calcium levels and thus alleviate the mitochondrial damages, however, RR reduced the apigenin-induced redox imbalance. Furthermore, apigenin induced apoptosis activation marked by the phosphatidylserine exposure, DNA fragmentation, and caspase activation. The pro-apoptotic effect of apigenin was counteracted by RR and NAC pretreatment. In particular, RR significantly reduced the pro-apoptotic responses. Conclusions: Apigenin isolated from A. yomena induced mitochondrial-mediated apoptotic pathway, and mitochondrial calcium signaling is main factor in its pathway in C. albicans . Graphical abstract: